DUKUNGAN ORANG TUA TERHADAP PENDIDIKAN ANAK TUNANETRA DI SEKOLAH DASAR LUAR BIASA KOTA BANDA ACEH - Warhamni Rahimi; Syaiful Bahri; Fajriani Fajriani (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2019)
Parental support is very important in obtaining the success of children's education. This study is intended to determine the form of parental support towards the education of blind children. This study used descriptive method with qualitative approach. The subject of this study was all parents who have blind children that attended Elementary school for special need children of Banda Aceh and Elementary school for special need children of Bukesra which was 6 people. Meanwhile the object of this study was the parental support towards the education of blind children. The data of this study were collected through interview. The results showed that all parents gave support toward the education of blind children. The parental support was showed in forms of Emotional Support, Esteem Support, Instrumental Support, Informational Support and Network Support. The support begins with the acceptance of children with limited conditions, helping the children in learning, caring about learning outcomes, paying attention the children's schoolwork, spending time with the children, giving awards, motivating the children in learning, giving advice and direction, and build a sense of togetherness with family and environment. However, the instrumental support such as the learning needs that parents provided to children was not fully maximized. Parents only used the learning facilities from the school. In addition, the financial issues became the cause of the child's learning needs were not fulfilled. From the results of the study, the researcher hopes that parents can continue to develop the support of the children's education, so that the children can develop all their potential and more motivated to be more success in terms of academic and non-academic, and provides learning facilities that support the development of education of blind children. Keywords: Parental Support, Education, Blind Children Abstrak: Dukungan orang tua sangat penting dalam mewujudkan keberhasilan pendidikan anak Penelitian ini bertujuan untuk mengetahui bentuk dukungan orang tua terhadap pendidikan anak tunanetra. Jenis Penelitian yang digunakan metode deskriptif dengan pendekatan kualitatif. Subjek dalam penelitian adalah semua orang tua yang memiliki anak tunanetra yang bersekolah di SDLB Negeri Banda Aceh dan SDLB Bukesra yang berjumlah 6 orang. Sedangkan objek penelitian adalah dukungan orang tua terhadap pendidikan anak tunanetra. Pengumpulan data dilakukan melalui wawancara. Hasil penelitian menunjukkan bahwa keseluruhan orang tua memberikan dukungan terhadap pendidikan anak tunanetra. Dukungan orang tua diwujudkan dalam bentuk, Emotional Support, Esteem Support, Instrumental Support, Informational Support dan Network Support. Dukungan tersebut diawali dengan penerimaan anak dengan kondisi keterbatasan, membantu anak dalam belajar, peduli terhadap hasil belajar, memberikan perhatian terhadap tugas sekolah anak, meluangkan waktu bersama anak, memberikan penghargaan, memotivasi anak agar semangat dalam belajar, memberikan nasehat dan arahan, menumbuhkan rasa kebersamaan dengan keluarga dan lingkungan. Namun Instrumental Support seperti kebutuhan belajar belum sepenuhnya maksimal orang tua berikan kepada anak. Orang tua hanya memanfaatkan fasilitas belajar dari sekolah. Selain itu keterbatasan ekonomi menjadi penyebab tidak terpenuhi kebutuhan belajar anak. Dari hasil penelitian diharapkan orang tua terus tingkatkan dukungan terhadap pendidikan anak, agar anak mengembangkan segala potensi yang dimilikinya dan lebih termotivasi untuk lebih maju dan berprestasi baik dari segi akademik dan non akademik, serta menyediakan fasilitas belajar yang mendukung perkembangan pendidikan anak tunanetra.Kata Kunci: Dukungan orang tua, Pendidikan, Anak tunanetra